Campus Medius: Digital Mapping in Cultural and Media Studies - Ganahl, Simon (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
Campus Medius explores and expands the possibilities of digital cartography in cultural and media studies. Simon Ganahl documents the development of the project from a historical case study to a mapping platform. Based on the question of what a media experience is, the concepts of the apparatus (dispositif) and the actor-network are translated into a data model. A time-space of twenty-four hours in Vienna in May 1933, marked by a so-called "Turks Deliverance Celebration" (Türkenbefreiungsfeier), serves as an empirical laboratory. This Austrofascist rally is mapped from multiple perspectives and woven into media-historical networks, spanning from the seventeenth century up to the present day.Website: https://e-book.fwf.ac.at/o:1733Buch German: https://e-book.fwf.ac.at/o:1734Buch English: https://e-book.fwf.ac.at/o:1735